2011
DOI: 10.1111/j.1460-9592.2011.03703.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized crossover comparison between the Laryngeal Mask Airway‐Unique and the air‐Q Intubating Laryngeal Airway in children*

Abstract: The ILA had higher airway leak pressures and superior fiberoptic grades of view when compared with the LMA-U and can be a suitable alternative to the LMA-U in children weighing 10-15 kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
54
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(79 citation statements)
references
References 25 publications
15
54
3
Order By: Relevance
“…The devices demonstrated similar airway leak pressures and overall clinical performance. The overall insertion success rates were similar to those reported by other randomised trials with the air-Q, LMA Unique, and classic LMA in children [4,13,14]. The airway tube of the air-Q SP is more flexible than the LMA Unique and could affect the subjective ease of placement, but insertion times were still faster with the air-Q SP.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The devices demonstrated similar airway leak pressures and overall clinical performance. The overall insertion success rates were similar to those reported by other randomised trials with the air-Q, LMA Unique, and classic LMA in children [4,13,14]. The airway tube of the air-Q SP is more flexible than the LMA Unique and could affect the subjective ease of placement, but insertion times were still faster with the air-Q SP.…”
Section: Discussionsupporting
confidence: 71%
“…The airway leak pressures of the air-Q SP in this study were also similar to those reported with both the size-2 air-Q with an inflatable cuff [4,6] and the size-2 air-Q SP [7] in children, but lower than in adult patients [3,17]. The LMA Unique airway leak pressures at 10 min in this study were higher than with other randomised trials on the paediatric-sized classic LMA [14,18,19], and LMA Unique [13,16].…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In addition, gastric tube passage was straightforward and deemed to be easy with the Aura Gain. The speed of insertion and insertion success rates of gastric tube placement are similar to our previous studies on the LMA Supreme [5,6,8,19]. Of note, the size 1.5 AuraGain allows for the use of a larger sized gastric tube than the size 1.5 Supreme (8 Fr vs 6 Fr), which could be advantageous for the evacuation of gastric contents.…”
Section: Discussionsupporting
confidence: 69%
“…Third, analysis of certain positive pressure ventilation parameters such as estimates of inspired to expired tidal volume ratios and leak fractions was not formally evaluated. Finally, this study may serve as the first evaluation on the use of the AuraGain in children, and future prospective comparison trials are needed, when all *Ease of device insertion as graded by the following subjective scale: 1 = no resistance; 2 = minimal resistance; 3 = moderate resistance; 4 = unable to place device [6,19] †Grade 1, larynx only seen; 2, larynx and epiglottis posterior surface seen; 3, larynx and epiglottis tip of anterior surface seen, less than 50% visual obstruction of epiglottis to larynx; 4, epiglottis downfolded and its anterior surface seen, greater than 50% visual obstruction of epiglottis to larynx; 5, epiglottis downfolded and larynx cannot be seen directly [10]. ‡Ease of gastric tube insertion as graded by the following subjective scale: 1 = easy, 2 = difficult, 3 = unable to pass [6].…”
Section: Discussionmentioning
confidence: 99%